Facilitating Interactive Evaluation Practice: Engaging Stakeholders Constructively. Issue 149 (March 2016) - Stevahn, Laurie; King, Jean A.
Abstract: This chapter introduces interactive evaluation practice (IEP) and its potential for grounding thinking about the foundational nature of interaction in evaluation studies and the role of facilitation in this process. It begins by defining key terms and elaborating specifically on IEP as an evaluator orientation for grounding and guiding decisions, actions, and reflections—all leveraged toward conducting meaningful studies. It then presents an evaluator's dozen of strategies useful for facilitating interaction among stakeholders to accomplish targeted aims and concludes by illustrating how evaluators can successfully facilitate these strategies in practice.